Unveiling Stories of Student Leaders in Their Academic and Non-Academic Journey - Larry C. Bercilla; Arnel L. Mamac; Jenybabe M. Palingcod; Mary Mae M. Plasquita (Journal of Learning and Educational Policy, 2023)
This study explored the experiences of student leaders and their perspectives on how they dealt the challenges associated with managing their academic and non-academic journeys. The focus was on student leaders at UM Tagum College, coping mechanisms, and insights that can be shared with the community. The study utilized a qualitative design, encompassing 14 participants; likewise, thematic analysis was employed to examine the participants' responses. Results show numerous challenges experienced by the participants as they engaged in both leadership roles and academics. Additionally, participants shared various coping mechanisms and valuable insights related to their experiences.